JALANGE COMMUNITY RESPONSE TO BAZNAS ZAKAT MANAGEMENT (A CASE STUDY AT BAZNAS IN BARRU) - arvina arvina; Muh. Yasin Soumena; Firman; Andi Rio Makkulau Wahyu (Indonesia Journal Of Zakat And Waqf, 2022)
BAZNAS Barru Regency is one of the best Amil Zakat Boards in South Sulawesi with achievements as the largest collection of zakat, infaq, and alms. BAZNAS Barru Regency is a zakat institution that assists in the collection, distribution and utilization of zakat in Barru Regency. Muzakki in Jalange pay zakat at BAZNAS in Barru Regency through UPZ because Muzakki understands that BAZNAS's task is to manage zakat, but in terms of collection, distribution and utilization of muzakki, they do not know the system used by BAZNAS. This study aims to determine the response of the Jalange community to the management of BAZNAS zakat in Barru Regency. This study uses qualitative research with a phenomenological approach and in collecting data using field research methods. The results showed that the BAZNAS zakat collection system in Barru Regency was: through salary deductions, UPZ, via transfer and direct collection. The Jalange community said the system made it easier for muzakki to pay zakat. The zakat distribution system for BAZNAS in Barru Regency is: distribution for zakat asnaf and the BAZNAS program. The Jalange community said the system was in accordance with Islamic law. The zakat utilization system of BAZNAS Barru Regency is: productive economic utilization and Community Development (ZCD) zakat. The Jalange community said that the utilization could help the mustahik economy in the long term.